INFORMATION TECHNOLOGY IN ASSESSMENT - MISUTOVA, Maria; MISUT, Martin (Trends in education, 2014)
This article describes the part of the solution of effective assessment with the support of technology. It is a part of complex solution containing a model of teaching invention, which includes the assessment with the support of technology, verification of the model by implementing in selected pilot subjects, model adaptation based on the results of the experiment, and development of recommendations and application in other subjects of study at the MTF STU in Trnava. Database tasks and design of tests for pilot subjects are parts of the teaching model, as well. Enhancement of the education quality achieved by knowledge assessment and evaluation, as well as standardizing knowledge level of students, are the expected outcome of the project.
Keywords: ICT; quality education; mathematics.